Measurements of N2+ ions in an inductively coupled plasma using saturated cavity ringdown spectroscopy - Rogers, SDA; Kniebe-Evans, C; Peverall, R; Hancock, G; Rhodes, BJ; Ritchie, G (IOP Publishing, 2024)
This paper presents a unique study of the bulk plasma characteristics in a low pressure inductively coupled nitrogen plasma. Saturated cavity ringdown spectroscopy (sat-CRDS) has been used to determine the absolute number densities and translational temperatures of N2+(X, ν = 0). The effect of saturation is readily accounted for by using an effective saturation parameter, Seff, and determined by a simple method employing measurements at two different gain settings of the detection system. The appropriateness of this method is confirmed by comparison with fitting individual ringdown data using a time-dependent saturation parameter, S(t), within the local approximation model for sat-CRDS; the two methods are in excellent agreement in returning absolute number densities and translational temperatures. N2+(X, ν = 0) number densities are determined across a matrix of pressure (10 − 100 mTorr) and rf power (200 − 400 W) conditions with maximum number densities of ca. 1.3 × 1010 cm−3 while translational temperatures range from 600 − 1500 K.